Prevalence and Risk Factors Associated with Multidrug Resistance and Extended-Spectrum β-lactamase Producing E. coli Isolated from Healthy and Diseased Cats - Mahmoud Fayez; Ahmed Elmoslemany; Ahmad A. Al Romaihi; Abdulfattah Y. Azzawi; Abdullah Almubarak; Ibrahim Elsohaby (MDPI AG, 2023)
Household cats have been identified as potential antimicrobial resistance (AMR) reservoirs, and the extended-spectrum β-lactamases (ESBL) producing E. coli circulating among cats has been more frequently reported globally, but the factors linked to its colonization remain poorly understood. Thus, the objectives of this study were to determine E. coli shedding and the occurrence of multidrug resistant (MDR)- and ESBL-producing E. coli, as well as to determine risk factors associated with colonization of MDR and ESBL-producing E. coli isolated from both healthy and diseased cats in the Eastern Province of Saudi Arabia. In a cross-sectional study, 2000 swabs were collected from five anatomical regions (anus, skin, ear canal, nares, and conjunctival sac) of 209 healthy and 191 diseased cats that were admitted to a veterinary clinic in the Eastern Province of Saudi Arabia. In addition, each cat owner filled out a questionnaire about their cat's demographics, management, health status, and antimicrobial usage. E. coli was detected in 165 (41.3%) of all cats, including 59 (28.2%) healthy and 106 (55.5%) diseased cats. In total, 170 E. coli isolates were found in healthy (35.3%) and diseased (64.7%) cats. Susceptibility testing revealed that 123 (72.4%) of the E. coli isolates were resistant to at least one of the tested antimicrobials. Overall, 17.6% (30/170) of E. coli isolates were MDR, with 10 (5.9%) and 20 (11.8%) isolates found in healthy and diseased cats, respectively. However, only 12 (7.1%) E. coli isolates were resistant to cefotaxime and harbored the blaCTX-M gene (ESBL-producer), with seven (4.1%) in healthy and five (2.9%) in diseased cats. Risk factor analysis showed that the odds of MDR and ESBL-producing E. coli were (20 and 17) and (six and eight) times higher when the family and cats were previously treated with antimicrobials, respectively. The presence of a child in the cat's family was also linked to an increased risk of MDR E. coli colonization (OR = 3.4). In conclusion, a high frequency of MDR and ESBL-producing E. coli was detected among healthy and diseased cats in Saudi Arabia, raising concerns about transmission to humans and supporting the need of a "One Health" approach to address the potential threats of cats as AMR reservoirs.